Study the Opportunities of Iranian Pharmaceutical Industry in Azerbaijan - Omid Moharrami Moghanlou; Pooria Abediasl; Leila Rezaie Shirmard; Abbas Kebriaee Zade; Akbar Abdolahiasl; Mona Jaberidoost (Tehran University of Medical Sciences, 2024)
Background: The economic, political, and geographical landscapes of certain neighboring countries of Iran have created potential opportunities and capacities that, if effectively harnessed, can propel Iran towards rapid economic growth and development. Azerbaijan, owing to its geographic proximity with a 765-kilometre border with Iran and numerous cultural ties, stands out as one of the most promising commercial opportunities for Iran. Methods: This study unfolds in five overarching stages. Initially, an examination of published texts and articles is conducted to identify challenges and opportunities. Subsequently, interviews with experts are conducted to refine and supplement the questionnaire to identify challenges and opportunities and encapsulate factors influencing drug exports from Iran to Azerbaijan. Following this, a structured questionnaire is developed based on the extracted factors from the preceding stages, and interviews with experts are conducted using the structured questionnaire. Finally, the results obtained are analyzed using the Simple Additive Weighting (SAW) method to facilitate the enhancement of drug exports from Iran to Azerbaijan. Results: After scrutinizing the infrastructure and opportunities for drug exports to Azerbaijan, we have reached fourteen influential factors, and after ranking the factors influencing pharmaceutical exports to Azerbaijan, it becomes evident that market and sales-related factors, laws, and regulations, as well as quality and supply chain considerations, respectively, are among the most significant factors affecting drug exports from Iran to Azerbaijan. Conclusion: The study has suggested that most important factors that affect the Iran- Azerbaijan pharmaceutical business market research, price differentials, and networking with influential individuals in Azerbaijan, it provided effective strategies for enhancing pharmaceutical exports to Azerbaijan. Furthermore, internal challenges within Iranian pharmaceutical companies, including regulatory compliance, quality assurance, and limited international certifications, underscored the necessity for cohesive collaboration between governmental entities and private enterprises to streamline export processes and enhance competitiveness in the global market.